Inadequate use of misoprostol. A public health problem?. - Isaza, Carolina; Saldarriaga, Wilmar; Pachajoa, Harry (Colombia Medica, 2008)
Introduction: The prenatal exposition to misoprostol during the first trimester has been associated to congenital malformations. In the last years it has been reported an increase in the detection of defects by vascular disruption associated with prenatal exposition of misoprostol. Methods: It is described the phenotypic characteristics of 7 new patients born in Cali, who consulted the dysmorphology clinic of the HUV since May of 2005 due to the presence of congenital malformations associated with prenatal exposition to misoprostol. Results: The final diagnoses of the 9 patients included in this study are: Moebius syndrome (3), hypoglosia-hypodactilia syndrome (1), cyclopia (1), gastroschisis (1), microcephaly (1), Klippel Fiel sequence (1) and hydranencephaly (1). The exposition to misoprostol appeared during gestation weeks 4 to 14 to doses between 800 and 1,000 mg, Discussion: Recently 11 cases of congenital malformations related to the exposition to misoprostol had been reported in this hospital. These cases were discovered in a period of 4 years; now the present paper reports 7 new cases in a period of 2 years. This fact suggests an increasing tendency to congenital malformations due to the association with misoprostol used as an abortive during the first pregnancy trimester. The observed malformations do not correspond only to Moebius syndrome, but to other vascular disruption defects like gastroschisis, hypoglosia-hypodactilia and hydranencephaly.